Metagenome‐Guided Analogue Synthesis Yields Improved Gram‐Negative‐Active Albicidin‐ and Cystobactamid‐Type Antibiotics. Issue 41 (7th September 2021) - Wang, Zongqiang; Kasper, Amanda; Mehmood, Rabia; Ternei, Melinda; Li, Shaogang; Freundlich, Joel S.; Brady, Sean F.
Abstract: Natural products are a major source of new antibiotics. Here we utilize biosynthetic instructions contained within metagenome‐derived congener biosynthetic gene clusters (BGCs) to guide the synthesis of improved antibiotic analogues. Albicidin and cystobactamid are the first members of a new class of broad‐spectrum ρ‐aminobenzoic acid (PABA)‐based antibiotics. Our search for PABA‐specific adenylation domain sequences in soil metagenomes revealed that BGCs in this family are common in nature. Twelve BGCs that were bio‐informatically predicted to encode six new congeners were recovered from soil metagenomic libraries. Synthesis of these six predicted structures led to the identification of potent antibiotics with changes in their spectrum of activity and the ability to circumvent resistance conferred by endopeptidase cleavage enzymes. Abstract : Biosynthetic instructions contained within congener biosynthetic gene clusters (BGCs) have been used to guide the synthesis of improved antibiotic analogues. ρ ‐Aminobenzoic acid encoding BGCs cloned from soil metagenomes have guided the synthesis of albicidin and cystobactamid analogues that show increased potency, different spectra of activity, as well as the ability to circumvent resistance conferred by endopeptidase cleavage enzymes.